Evaluation of infection following the use of 3D printed polyetheretherketone facial implants in repair of maxillofacial deformities - احمد, احمد; يعقوب , حكمت; خليل , علي (Latakia University Journal -Medical Sciences Series, 2022)
Objective: This study aims to evaluate early and late infection after using of facial implants manufactured specifically for the patient using 3D printing technology in the reconstruction of maxillofacial deformities. Materials and methods: The research sample consisted of 10 patients suffering from deformities at the face (traumatic patients in the maxillary region who suffer from physical deficiency defects in hard tissues, oncology patients who were subjected to a previous surgical procedure in the region of the orbital region, upper jaw, chin, and This resulted in a physical deficiency in the bone, chin retraction, congenital malformations patients, half-facial deficiency syndrome patients) between 2020 and 2021 in the Department of Oral and Maxillofacial Surgery at Tishreen University Hospital - Lattakia - Syria. All patients underwent a CT scan Computerized using a device provided that a large number of sections are available (more than 200 sections in each axis) and the thickness of the section is less than 1 mm with an accuracy of 64 bit, then a design was made for the required facial implant in coordination between the designer and the surgical team. peek material, and then performing surgical operations for patients under general anesthesia according to the appropriate surgical approach and fixing the implants by titanium screws with antibiotic coverage. They were followed up regularly after surgery a week, one month and three months to make sure there were signs of infection. Results: A late infection was observed in only one case within the chin area without a response to drug treatment, which prompted us to perform a surgical procedure to remove the facial implant with an infection rate of 10%.